2023
DOI: 10.1021/acsomega.3c00502
|View full text |Cite
|
Sign up to set email alerts
|

Metal–Support Interactions in Heterogeneous Catalysis: DFT Calculations on the Interaction of Copper Nanoparticles with Magnesium Oxide

Abstract: Oxide supports play an important role in enhancing the catalytic properties of transition metal nanoparticles in heterogeneous catalysis. How extensively interactions between the oxide support and the nanoparticles impact the electronic structure as well as the surface properties of the nanoparticles is hence of high interest. In this study, the influence of a magnesium oxide support on the properties of copper nanoparticles with different size, shape, and adsorption sites is investigated using density functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…The calculations were performed using the gamma point of the reciprocal space. As mentioned earlier, the behavior of the MgO(100) surface was mimicked using a 3 Â 3 trilayer periodic slab, as in previous works, 23,47 with the deepest layer fixed to represent the bulk. 48 This methodology is shown to be reliable in previous studies by several groups.…”
Section: Methodsmentioning
confidence: 99%
“…The calculations were performed using the gamma point of the reciprocal space. As mentioned earlier, the behavior of the MgO(100) surface was mimicked using a 3 Â 3 trilayer periodic slab, as in previous works, 23,47 with the deepest layer fixed to represent the bulk. 48 This methodology is shown to be reliable in previous studies by several groups.…”
Section: Methodsmentioning
confidence: 99%
“…The latter can be calculated using the finite difference method or modeled by the deep learning surrogate model [63,65]. 'Catalyst support' strongly affects the bulk part of the nanoparticle through charge flow and strong support interaction, which can be computationally determined easily and effectively by density functional theory (DFT) calculations [62,75]. The total pressure and temperature, along with the cell geometry, strongly affect the coverage and, therefore, the chemistry part of the whole model output [60].…”
Section: System Functional Decompositionmentioning
confidence: 99%
“…Meanwhile, MgO as an electronic promoter can affect the adsorption strength of the reactive intermediates via modulating the electronic structure of the active sites of Cu-based catalysts, improving methanol formation. , The research by Nielsen et al shows that there is a synergistic interaction between Cu and MgO and that the promotion of CO hydrogenation is mainly due to a bifunctional mechanism at the metal/support interface, where the interfacial formate generated by the reaction of CO with basic hydroxyls is an important intermediate for methanol formation. Hakimioun et al used the nonreducible oxide support MgO as an example and found that there is no significant influence of the MgO support on the electronic structure of the copper nanoparticles, with the exception of adsorption directly at the Cu–MgO interface. The oxygen adsorption energies at the Cu/MgO interface are about ∼0.6 eV stronger, both for the interfaces of Cu 192 /MgO and Cu NW / MgO.…”
Section: Introductionmentioning
confidence: 99%